Radar-guided robot - Wang, Jiajun (2014)
Since the first electronic autonomous robot was created in 1950s, the impact of robots on industry and society grows rapidly. Especially in modern world, as the technology develops, sufficient researches on robotic system are required to fulfill the increasing demand on the work which human may not able to easily accomplish.